Vie et miracles de Daniel de Qorqor. Introduction - Gérard Colin (Afriques)
The Life and the miracles of Daniel of Qorqor are currently known through two manuscripts preserved in the church of Māryām Qorqor in Tigray. The first, dated to 1911 A.D., is available only on a microfilm kept at the Institute of Ethiopian Studies in Addis Ababa. This copy of poor quality, incomplete and sometimes difficult to read, is unsuitable for a complete edition. The other manuscript, photographed in 2009 in the church, is edited here and translated in its entirety. Completed in 1975-76, it presents a substantially different version of the first manuscript, both from a formal point of view and with regard to factual information. This introduction presents similarities and differences, especially concerning the monastic genealogy of Daniel.